Intrinsic and Extrinsic Factors Affecting the Color Stability of Resin Cements - López-Pérez , Janira T. (Mexican Journal of Medical Research ICSA, 2025)
Resin cements play a fundamental role in the adhesion of indirect restorations in dentistry; however, their color stability is a concern for every dentist, especially in the aesthetic context. Traditional resin cements contain tertiary amines as polymerization co-initiators, which can influence color change over time. In response to this limitation, amine-free resin cements have been developed to improve color stability. However, it should be taken into account that this type of cement also has its limitations. The absence of amines may reduce the rate and degree of conversion, potentially compromising the material’s integrity. In addition, some photoinitiators are not compatible with all curing lights available on the market, among other limitations. This article analyzes the factors that influence the color change of these cements, including internal factors such as the composition of the organic and inorganic matrix, and external factors such as exposure to staining agents. The changes that these types of cements undergo can be detected through the CIE Lab® system, one of the most widely used methods for color evaluation.